2005
DOI: 10.1016/j.atmosenv.2005.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic properties of urban street dust and their relationship with organic matter content in the West Midlands, UK

Abstract: This study demonstrates significant correlations between the organic matter content of urban street dust and certain mineral magnetic properties, which accords with previous work that indicates magnetic parameters offer potential as a proxy for organic content. However, site-specific data demonstrate the relationship can be different for particular roads, even within the same area. This indicates the association may be more complex than previous work proposes and a cautionary note is required. It is recommende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(51 citation statements)
references
References 41 publications
1
49
0
1
Order By: Relevance
“…Thompson and Oldfield, 1986). Numerous studies have demonstrated that magnetic techniques can be successfully used to monitor anthropogenic or geoanthropogenic pollution from surface soils (Dearing et al, 1996b;4 Jordanova et al, 2003;Qiao et al, 2011;Zheng and Zhang, 2008;Zhu et al, 2010), fossil fuel combustion (Heller et al, 1998), coastal areas (Dong et al, 2014;Zhang et al, 2009), urban dust (Bucko et al, 2011;Shilton et al, 2005;Shu et al, 2000;Xie et al, 1999;Zhu et al, 2010) and historical monuments (Schiavon and Zhou, 1996). Zhang et al (2012) show the first example for the use of magnetic measurements in detecting the iron-containing particles in the Shanghai subway system.…”
Section: Introductionmentioning
confidence: 99%
“…Thompson and Oldfield, 1986). Numerous studies have demonstrated that magnetic techniques can be successfully used to monitor anthropogenic or geoanthropogenic pollution from surface soils (Dearing et al, 1996b;4 Jordanova et al, 2003;Qiao et al, 2011;Zheng and Zhang, 2008;Zhu et al, 2010), fossil fuel combustion (Heller et al, 1998), coastal areas (Dong et al, 2014;Zhang et al, 2009), urban dust (Bucko et al, 2011;Shilton et al, 2005;Shu et al, 2000;Xie et al, 1999;Zhu et al, 2010) and historical monuments (Schiavon and Zhou, 1996). Zhang et al (2012) show the first example for the use of magnetic measurements in detecting the iron-containing particles in the Shanghai subway system.…”
Section: Introductionmentioning
confidence: 99%
“…The decision to analyse only the <63 µm fraction was because these particles are easily transported in suspension, with the finest capable of remaining airborne for considerable durations. Samples were then weighed and prepared for analysis [14].…”
Section: Sample Collectionmentioning
confidence: 99%
“…Compared with other analytical methods mineral magnetics provides a compositional tool, which is reliable, rapid, non-destructive, inexpensive and sensitive to low detection levels [11]. Consequently, this has assisted understanding linkages between health and respirable airborne particulate matter [12], association with organic matter [13,14], progressed spatial and temporal pollution studies [15,16], benefited air-borne particulate discrimination [16,17] and highlighted its suitability for aiding biomonitoring of air quality [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these investigations, mineral magnetic measurements have been identified as a suitable proxy for geochemical, radioactivity, organic matter content and particle size data (Bonnett et al 1988;Oldfield et al 1993;Hutchinson and Prandle 1994;Clifton et al 1997Clifton et al , 1999Xie et al 1999Xie et al , 2000Zhang et al 2001;Booth et al 2005a;Shilton et al 2005).…”
Section: Introductionmentioning
confidence: 99%